2021
DOI: 10.3390/microorganisms9061301
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Extracellular DNA Promotes β-Amyloid Aggregation

Abstract: Alzheimer’s disease is associated with prion-like aggregation of the amyloid β (Aβ) peptide and the subsequent accumulation of misfolded neurotoxic aggregates in the brain. Therefore, it is critical to clearly identify the factors that trigger the cascade of Aβ misfolding and aggregation. Numerous studies have pointed out the association between microorganisms and their virulence factors and Alzheimer’s disease; however, their exact mechanisms of action remain unclear. Recently, we discovered a new pathogenic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…Therefore, further exploration of these issues is also the next step of our study. Third, extracellular bacterial DNA has been shown to play an important role in protein misfolding ( Tetz et al, 2020 ; Tetz and Tetz, 2021 ), yet the current study did not analyze whether fecal transplantation increases extracellular bacterial DNA in plasma, so this will be a direction for our future research. Finally, the specific communication pathways between brain and gut microbiota are not fully understood, and how TMAO causes ER stress in the cerebral cortex is unclear, so more in-depth studies are needed to test and verify our findings.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, further exploration of these issues is also the next step of our study. Third, extracellular bacterial DNA has been shown to play an important role in protein misfolding ( Tetz et al, 2020 ; Tetz and Tetz, 2021 ), yet the current study did not analyze whether fecal transplantation increases extracellular bacterial DNA in plasma, so this will be a direction for our future research. Finally, the specific communication pathways between brain and gut microbiota are not fully understood, and how TMAO causes ER stress in the cerebral cortex is unclear, so more in-depth studies are needed to test and verify our findings.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, given the recently discovered ability of DNA molecules to modify and misfold proteins, it is intriguing whether TezRs could possess a similar chaperoning function [32,[143][144][145]. Recently, we discovered the existence of a similar regulatory system in eukaryotes [45].…”
Section: Discussionmentioning
confidence: 99%
“…We also found Gram-negative bacterial DNA in AD and aging brains. Recent studies demonstrated that bacterial DNA promotes aggregation of β-amyloid and tau, two hallmarks of AD pathology (Tetz et al, 2020 ; Tetz and Tetz, 2021 ). The DNA was derived from Porphyromonas gingivalis, Burkholderia burgdorferi , and different strains of E. coli , all of which are gram-negative and have been associated with AD (Tetz et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%